2012
DOI: 10.1136/bmjopen-2011-000494
|View full text |Cite
|
Sign up to set email alerts
|

Decreased prevalence of diabetes in marijuana users: cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) III

Abstract: ObjectiveTo determine the association between diabetes mellitus (DM) and marijuana use.DesignCross-sectional study.SettingData from the National Health and Nutrition Examination Survey (NHANES III, 1988–1994) conducted by the National Center for Health Statistics of the Centers for Disease Control and Prevention.ParticipantsThe study included participants of the NHANES III, a nationally representative sample of the US population. The total analytic sample was 10 896 adults. The study included four groups (n=10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 22 publications
10
105
5
Order By: Relevance
“…Of those studies reporting significant negative correlations, two reported that longer duration of Cannabis use was associated with reduced BMI , Rajavashisth et al, 2012.…”
Section: Results: Bmi Datamentioning
confidence: 99%
See 3 more Smart Citations
“…Of those studies reporting significant negative correlations, two reported that longer duration of Cannabis use was associated with reduced BMI , Rajavashisth et al, 2012.…”
Section: Results: Bmi Datamentioning
confidence: 99%
“…There is some evidence for this, but results are inconsistent. Multiple studies have reported in Cannabis users reduced rates of diabetes mellitus, insulin insensitivity, or metabolic syndrome in fully adjusted models including age (Rajavashisth et al, 2012, Ngueta et al, 2015, Alshaarawy and Anthony, 2015, Penner et al, 2013, Thompson and Hay, 2015, Waterreus et al, 2016. Yankey et al (Yankey et al, 2016) also reported decreased DM rates (AOR 0.42) that did not reach statistical significance (95% CI = 0.13 -1.36).…”
Section: Observations Supporting This Theorymentioning
confidence: 93%
See 2 more Smart Citations
“…In 2012, Rajavashisth and coworkers [25] analyzed data collected by the National Health and Nutrition Examination Survey and found that current light marijuana users have lower diabetes prevalence than current heavy users and past marijuana users, Figure 2. Also, all marijuana users (past or current) are less likely to be diagnosed as diabetes compared to non-marijuana users ( Figure 2) after adjustment with confronting factors such as age, race and alcohol use.…”
Section: 2epidemiological Studies That Link Cannabinoid and Decreasmentioning
confidence: 99%